Escape the debt trap let the Lord lead you out - Hood, Kregg (Ft. Worth, TX : Prime Source Providers, 2003)
Presents a faith-based approach to getting out of debt.
How to lead "Escape the debt trap" -- Where do we go from here? -- Let's get started -- Prescription for financial health.
Title from container.
In container (23 cm.).
Sermons by Dr. Kregg Hood.
Keywords: Finance, Personal; Debt; Consumer credit